Attitudes, knowledge and practices concerning delirium: a survey among intensive care unit professionals. Issue 3 (20th March 2016) - Trogrlić, Zoran; Ista, Erwin; Ponssen, Huibert H; Schoonderbeek, Jeannette F; Schreiner, Frodo; Verbrugge, Serge J; Dijkstra, Annemieke; Bakker, Jan; van der Jagt, Mathieu
ABSTRACT: Background: Delirium is a common form of vital organ dysfunction in intensive care unit (ICU) patients and is associated with poor outcomes. Adherence to guideline recommendations pertaining to delirium is still suboptimal. Aims: We performed a survey aimed at identifying barriers for implementation that should be addressed in a tailored implementation intervention targeted at improved ICU delirium guideline adherence. Design: The survey was conducted among ICU professionals. Methods: An online survey was conducted among 360 ICU health care professionals (nurses, physicians and delirium consultants) from six ICUs in the southwest of the Netherlands as part of a multicentre prospective implementation project [response rate: 64% of 565 invited; 283 (79%) were nurses]. Results: Although the majority (83%) of respondents considered delirium a common and major problem in the ICU, we identified several barriers for implementation of a delirium guideline. The most important barriers were knowledge deficit, low delirium screening rate, lack of trust in the reliability of delirium screening tools, belief that delirium is not preventable, low familiarity with delirium guidelines, low satisfaction with physician‐described delirium management, poor collaboration between nurses and physicians, reluctance to change delirium care practices, lack of time, disbelief that patients would receive optimal care when adhering to the guideline and the perception that the delirium guideline is cumbersome or inconvenient in daily practice. Conclusion: Although ICU professionals consider delirium a serious problem, several important barriers to adhere to guidelines on delirium management are still present today. Relevance to clinical practice: Identification of implementation barriers for adherence to guidelines pertaining to delirium is feasible with a survey. Results of this study may help to design‐targeted implementation strategies for ICU delirium management.